Investigation of parental socioeconomic status as a determinant of dietary habits and disease severity of sickle cell disease children - Abisola Alaka , Anuoluwapo; Abolape Iyanda , Ayobola (International Journal of Biological Research, 2024)
Background: Socioeconomic status (SES) impacts dietary choices and poor dietary pattern has been reported to play a role in the etio-pathogenic mechanisms that give rise to various diseases. Objective: The study is designed to explore the relationship between parental SES and both the dietary habits and disease severity markers among sickle cell disease (SCD) pediatric patients. Methods: Participants’ hemoglobin genotypes and hematocrit levels were determined using standard methods. Questionnaire was administered to the participants to obtain information on qualitative parameters. Descriptive and inferential statistics were used for data analysis. Significant level was set with P < .05. Results: A high percentage of parents of SCD participants were of medium to high SES [73.33%- HbSC; 64.29%- HbSS]. While the rates of hospitalization of HbSS (92.85%) and HbSC (66.67%) were dissimilar, the rates of patients that had suffered vaso-occlusive crisis (VOC) in the last three months prior to the study were comparable [46.67%-HbSC; 53.57%-HbSS]. The daily fruit/vegetable consumption habits of 3 genotypes were poor ranging from 15-25%. The hematocrit levels of the 3 groups were significantly different. Conclusion: The study suggests that high percentage of patients belong to medium-high SES, signifying that educational background of parents did not impact prevalence of the disease.
Keywords: Disease Severity; Fruit/Vegetable Intake; Sickle Cell Disease; Socioeconomic Status.